A nexus between farmland rights, and access, demand, and amount of agricultural loan under the socialist system of China. (September 2022) - Gong, Maogang; Elahi, Ehsan
Abstract: In the modern socialist system of China, the governments separated land ownership rights and land use rights to increase the access and demand for agricultural loans for the improvement of the social welfare of farmers. Therefore, the current study aims to evaluate the impact of farmland rights and land transfer on access, demand, and amount of agricultural loan under the socialist system of China. For this purpose, data from China Household Finance Survey (CHFS) were used to empirically analyze the objectives of the study using various econometric approaches particularly, the Propensity Score Matching (PSM) method and Benchmark regression. Results depicted that farmland rights and land transfer-in positively and significantly impacted access, demand, and amount of loan. However, the land transfer-out reduced the demand for agricultural loan. Moreover, the land transfer-in found a positive mediating impact on access, demand, and amount of agricultural loan. While the negative mediating effect of the land transfer-out was only reflected in the access and demand for agricultural loan. The farm output of the previous year significantly and positively impacted availing the agricultural loan. While the age of farmers significantly and negatively impacted on availing the agricultural loan. The results also confirmed the regional differences regarding the impact of farmland rights and land transfer-out on availing the agricultural loan. Findings of the study suggest public authorities to increase capital input through state-owned farm assets to reduce the funding gaps and promote agro-environmental sustainability. Highlights: The study evaluates impact of farmland rights and land transfer on agricultural loan. Farmland rights & land transfer-in positively impacted on access & demand of the loan. Land transfer-out significantly reduced the demand for agricultural loan. Land transfer-in found with a positive mediating impact on agricultural loan. Regional difference was confirmed for impact of farmland rights on agricultural loan.